Peculiarities of occupational mental health care in kindergarten teachers - Otarbayeva, Zhansaya; Baizhumanova, Bibianar; Tuyakova, Ulbossyn; Mambetalina, Aliya; Umirzakova, Assem; Kulzhabayeva, Lyazzat (Frontiers in Psychology, 2023)
The purpose of this paper is to quantify the factors that disrupt the mental health of kindergarten (KG) teachers. For this, the researchers conducted an electronic survey of preschool teachers (n=587) on a popular educational platform with the Symptom Checklist-90-R and content analysis of interviews in practicing KG teachers (n=105) with an open discussion of the main stressors during professional activities. Self-reports indicated that depression, interpersonal sensitivity, and anxiety were the main mental health symptoms. ANOVA has revealed that total teaching experience is a statistically significant factor for the mental health of KG teachers: F(2.60)=5.99. According to respondents, the main stressors included concern for the children’s health, fear of injuries, and difficulties in communicating with parents. The synthesis of results allowed for proposing six specific steps for mental health care in KG teachers. The findings are important for administrators and officials of preschool education. The proposed approach can become a theoretical basis for finding ways of mental health care for practicing teachers in further research.